Free Flaps in a Resource Constrained Environment: A Five-Year Experience—Outcomes and Lessons Learned. (11th August 2015) - Nangole, Wanjala F.; Khainga, Stanley; Aswani, Joyce; Kahoro, Loise; Vilembwa, Adelaine
Abstract : Introduction . Free flap surgery is a routine procedure in many developed countries with good surgical outcomes. In many developing countries, however, these services are not available. In this paper, we audit free flaps done in a resource constrained hospital in Kenya. Objective . This is a five-year audit of free flaps done in a tertiary hospital in Kenya, between 2009 and 2014. Materials and Methods . This was a prospective study of patients operated on with free flaps between 2009 and 2014. Results . A total of one hundred and thirty-two free flaps in one hundred and twenty patients were performed during the five-year duration. The age range was eight to seventy-two years with a mean of 47.2. All the flaps were done under loupe magnification. The overall flap success rate was eighty-nine percent. Conclusion . Despite the many limitations, free flaps in our setup were successful in the majority of patients operated on. Flap salvage was noted to be low due to infrequent flap monitoring as well as unavailability of theatre space. One therefore has to be meticulous during surgery to reduce any possibilities of reexploration.